2014
DOI: 10.1002/elan.201400466
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Monitoring of the Diffusion Junction Potential in Speciation Studies by Polarography under very Acidic Conditions. Part II: The Quasi‐Reversible Cu(II)‐Picolinic Acid System

Abstract: The use of polarography to accurately determine stability constants of complexes formed under very acidic conditions (below pH 2) is demonstrated. The diffusion junction potentials, which must be accounted for below pH 2, were evaluated by applying protocols developed where Tl(I) is used as an internal reference. The Cu(II)-picolinic acid (2-pyridinecarboxylic acid) system studied was chosen since the CuL + species only exists in solution below pH 2 under the conditions used and literature data exists to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…37,38 Since we wanted to work at moderate ionic strengths so that formation constants generated could have some application to the biological field, a nitrate background was chosen as the compromise between solubility of hydrolysis products and reversibility of the reduction process. The successful study of quasi-reversible systems had been previously been demonstrated, 39,40 however, as will be discussed, in this work it was found that the DC reduction waves could actually be considered as reversible when working in 0.25 -0.5 M nitrate solutions.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…37,38 Since we wanted to work at moderate ionic strengths so that formation constants generated could have some application to the biological field, a nitrate background was chosen as the compromise between solubility of hydrolysis products and reversibility of the reduction process. The successful study of quasi-reversible systems had been previously been demonstrated, 39,40 however, as will be discussed, in this work it was found that the DC reduction waves could actually be considered as reversible when working in 0.25 -0.5 M nitrate solutions.…”
mentioning
confidence: 67%
“…The reduction of Tl(I) was fully reversible across the pH range, as noted before. 39,41 Although it was expected that Bi(III) reduction would be quasi-reversible in a nitrate medium, 30,45 the  values obtained were very close to one (typically 0.951.00) provided data points at the onset of mercury oxidation were omitted when fitting the wave. Therefore, since I d does not change with the extent of reversibility and E 1/2 is dependent on the steepness of the wave, which in this case is Nernstian (since   1 in Eq 2), the reduction of Bi(III) was considered as reversible for our purpose (see Section 2 of the Supporting Information for further discussion).…”
Section: Instrumentationmentioning
confidence: 92%
“…In previous studies, no complexation was observed for [PA T ]:[Tl T ] up to 100 for measurements made up to pH 8. 23,24 Figure 1 shows the plot of experimental E 1/2 (Bi) (○) vs pH where [PA T ]:[Bi T ] = 197, as well as the E 1/2 values after correction for E j (×). Both the E(Bi) and E c (Bi) values as determined for this experiment are also displayed.…”
Section: Resultsmentioning
confidence: 99%
“…It is thus important to include nitrate as a competing ligand especially in the pH range where these species are significant. Unfortunately, the 3D-CFC software used to determine stability constants from polarographic data (as applied in previous work (23,24)) can only accommodate two ligands simultaneously, one of which is always hydroxide and the other is the ligand being investigated. As a guide, the species distribution diagram (SDD) of 1 × 10 -5 M Bi(III) in 0.5 M nitrate (in the absence of PA) is shown on the secondary axis in Figure 1.…”
Section: Determining Stability Constants From Voltammetric Data Usingmentioning
confidence: 99%
See 1 more Smart Citation